Interproximal bone loss at contra-lateral teeth with and without root canal filling in periodontitis patients - Adyani-Fard, Dana; Kim, Ti-Sun; Eickholz, Peter (Journal of clinical periodontology, 2011)
Adyani-Fard D, Kim T-S, Eickholz P. Interproximal bone loss at contra-lateral teeth with and without root canal filling in periodontitis patients. J Clin Periodontol 2011; 38: 269-275. 38: 269-275. doi: 10.1111/j.1600-051X.2010.01657.x. Abstract Aim: The purpose of this study was to test the hypothesis that teeth that are adequately endodontically treated develop more periodontal bone loss than their contra-lateral counterpart without root canal filling (RCF) in relation to the restoration margin (RM) in periodontitis patients. Methods: In 53 periodontitis patients (26 females; 34-73 years of age), 66 pairs of radiographs were sampled. Each pair of radiographs depicted one pair of contra-lateral teeth: one with and one without RCF. All radiographs were digitized. Using a PC program the linear distances cemento-enamel junction (CEJ) or RM to the alveolar crest (AC) and CEJ/RM to bony defect (BD) were measured at the site of most pronounced bone loss. Comparisons were made according to RCF, RM, site (mesial/distal), jaw and tooth type (anterior/posterior). Results: The study showed statistically significant differences for the distance CEJ/RM-BD only for tooth type (anterior: 6.17±3.01 mm, posterior: 5.03±2.59 mm, p=0.044; without RCF: 5.14±2.82 mm, RCF: 5.57±2.70 mm, p=0.159; without RM: 5.67±2.98 mm, RM: 5.16±2.61 mm; p=0.322; mesial: 5.62±2.98 mm, distal: 5.06±2.24 mm; p=0.238; maxilla: 5.55±3.04 mm, mandible: 5.20±2.52 mm; p=0.486). Conclusions: Teeth with endodontic treatment failed to exhibit more bone loss than endodontically untreated teeth.
First published: 06 December 2010
Gesehen am 28.02.2022